Algorithmic bias: addressing growing concerns - Koene, Ansgar (IEEE, 2017)
In the context of the IEEE Global Initiative for Ethical Considerations in Artificial Intelligence and Autonomous Systems, and with support from its executive director, the author have proposed the development of a new IEEE Standard on Algorithmic Bias Considerations. The aim is for this to become part of a set of ethical design standards, such as the IEEE P7001™ Standards Project called Transparency of Autonomous Systems with a Working Group. Whereas the Transparency of Autonomous Systems Standard will be focused on the important issue of “breaking open the black box” for users and/or regulators, the Algorithmic Bias Standard is focused on “surfacing” and evaluating societal implications of the outcomes of algorithmic systems, with the aim of countering non-operationally-justified results.